Using phosphoproteomics and next generation sequencing to discover novel therapeutic targets in patient antibodies. (1st September 2020) - Zeneyedpour, Lona; Sten-van `t Hoff, Jenny; Luider, Theo
ABSTRACT: Introduction : The goal of this review is to survey proteomics and next generation sequencing (NGS) approaches to discover phosphopeptide neoantigens that can be used as targets for individualized cancer therapy and diagnostics. Neoantigens are peptides or proteins that can be derived from tumor-specific or viral alterations containing mutated sequences including different post-translational modifications that will not be found in normal human cells. These neoantigens can be highly specific for the individual affected tissue. Mass spectrometry combined with NGS allow identifying autoantibodies specific for neoantigens, including neoantigens that contain phosphorylated moieties. Areas covered : We discuss recognition of neoantigens through the application of phosphoproteomics. We focus on phosphoprotein modifications that can be accurately identified with mass spectrometry and can serve as rarely described targets for immunotherapy and diagnosis in cancer and autoimmune diseases. Identification of these phospho-moiety containing neoantigens gives the possibility to search for corresponding autoantibodies, especially if NGS and mass spectrometry are combined. Expert commentary : Identification of post-translational modifications with mass spectrometry gives possibilities to define modifications that are specific for cancer and autoimmune diseases. This technology develops rapidly, and gives opportunities to select neoantigens that are highly specific for cancer and immune diseases and to sequence autoantibodies involved.